#### Answer

$x=2$
$y=-1$
(2, -1)

#### Work Step by Step

$2x -y = 5$
$5x -y = 11$
Subtract the first equation from the second one.
$5x-y-(2x-y)=11-5$
$5x-2x-y+y=6$
$3x=6$
$x=2$
Substitute x in the first equation to get y
$2*2 -y=5$
$-y=5-4$
$y=-1$

Published by
Cengage Learning

ISBN 10:
1-13311-087-8

ISBN 13:
978-1-13311-087-3

$x=2$
$y=-1$
(2, -1)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.